Laparoscopic omentectomy in primary torsion of the greater omentum: report of a case - Jun Kataoka; Toshikatsu Nitta; Masato Ota; Yuko Takashima; Yuta Yokota; Kensuke Fujii; Takeshi Higashino; Takashi Ishibashi (Surgical Case Reports, 2019)
Abstract Background Torsion of the greater omentum is a rare cause of acute abdominal pain in adults and children. It is very difficult to make a correct diagnosis of torsion clinically because it mimics other acute pathologies; however, the preoperative diagnosis can be easily confirmed with the use of computed tomography (CT). Herein, we report a case of laparoscopic omentectomy for primary torsion of the omentum, which was not improved by conservative treatment. Case presentation A 50-year-old Japanese man presented to our hospital with acute right lower quadrant abdominal pain of a few hours’ duration. Routine blood tests showed a white blood cell count of 8900/mm3, and the C-reactive protein (CRP) level was 8.13 mg/dl. Contrast-enhanced CT scan of the abdomen revealed twisting of the omentum with a local mass of fat density and fluid distributed in a whirling oval-shaped mass pattern at the right flank and iliac fossa. Therefore, the patient was admitted to our hospital based on a diagnosis of omental torsion. The patient was treated with conservative treatment with analgesics, anti-inflammatories, and antibiotics. Although his symptoms were ameliorated, his laboratory and radiological findings worsened. We performed laparoscopic omentectomy 6 days after admission. The resected omentum was 24 cm × 22 cm in size and was twisted and dark red in color, suggesting infarction. Histological analysis revealed that the specimen was ischemic and hemorrhagic omentum, accompanied by inflammatory infiltration. The patient’s postoperative course was uneventful, and he was discharged 9 days later. Conclusion This is a rare case of primary torsion of the greater omentum that was treated successfully with laparoscopic omentectomy. Considering the increase in surgical difficulty due to inflammation from prolonged torsion and the limited efficacy of conservative treatment, we conclude that surgical intervention is warranted as early as possible when torsion of the greater omentum is suspected.